On Nonlinear Dynamics and Control of A Particular Portal Frame Foundation Model, Excited by a Non-Ideal Motor - Balthazar, José Manoel [UNESP]; Felix, Jorge Luis Palacios; Brasil, Reyolando Manoel Lopes Rabelo da Fonseca (Trans Tech Publications, 2003)
The nonlinear dynamic response and a nonlinear control method of a particular portal frame foundation for an unbalanced rotating machine with limited power (non-ideal motor) are examined. Numerical simulations are performed for a set of control parameters (depending on the voltage of the motor) related to the static and dynamic characteristics of the motor. The interaction of the structure with the excitation source may lead to the occurrence of interesting phenomena during the forward passage through the several resonance states of the systems. A mathematical model having two degrees of freedom simplifies the non-ideal system. The study of controlling steady-state vibrations of the non-ideal system is based on the saturation phenomenon due to internal resonance.
Keywords: Internal Resonance; Nonlinear Dynamics; Portal Frame; Saturation; Portal frames; Computer simulation; Control equipment; Degrees of freedom (mechanics); Electric motors; Mathematical models; Nonlinear control systems; Potential energy; Resonance; Rotating machinery; Rotors; Structural frames; Vibrations (mechanical); Materials science